Retinal Drug Delivery: Rethinking Outcomes for the Efficient Replication of Retinal Behavior - Eliana B. Souto; Elena Sanchez-Lopez; Joana R. Campos; Raquel da Ana; Marta Espina; Maria L. Garcia; Patrícia Severino; Fernando Batain; Thais F. R. Alves; Kessi M. M. Crescencio; Selma B. Souto; Marco V. Chaud (Applied Sciences, 2020)
The retina is a highly organized structure that is considered to be "an approachable part of the brain." It is attracting the interest of development scientists, as it provides a model neurovascular system. Over the last few years, we have been witnessing significant development in the knowledge of the mechanisms that induce the shape of the retinal vascular system, as well as knowledge of disease processes that lead to retina degeneration. Knowledge and understanding of how our vision works are crucial to creating a hardware-adaptive computational model that can replicate retinal behavior. The neuronal system is nonlinear and very intricate. It is thus instrumental to have a clear view of the neurophysiological and neuroanatomic processes and to take into account the underlying principles that govern the process of hardware transformation to produce an appropriate model that can be mapped to a physical device. The mechanistic and integrated computational models have enormous potential toward helping to understand disease mechanisms and to explain the associations identified in large model-free data sets. The approach used is modulated and based on different models of drug administration, including the geometry of the eye. This work aimed to review the recently used mathematical models to map a directed retinal network.